Social Piety Index for Character Building in Indonesia: A Case Study of The Society of Mojokerto City - Zainul Muhibbin; Sutikno; Soedarso; Imam Safawi Ahmad; Novianti Ika Sari (Jurnal Sosial Humaniora, 2022)
Since 2010, National Character Development has been a program. Thisnationwide initiative faces fairly significant issues due to the dynamics andchanges in the life patterns of individuals. To revitalize the national program,the national movement of mental revolution was then established in 2016. Thisprogram's implementation was crucial, but it did not appear to have a preciseevaluation system to measure its success. Therefore, a system of evaluationthat could generate index documents of the success rate was required. SocialPiety Index was the community behavior survey that had been conducted(Indeks Kesalehan Sosial-IKS). This survey examined the level of social pietyand produced a document with an index of accomplishments. Consequently,the IKS record may be utilized as a depiction of the evolution of thecommunity's character. Utilizing a quantitative approach with statisticalanalysis, the survey method employed was quantitative. The acquired resultrevealed that both the knowledge and attitude data were strong, but the levelof correlation between the two was poor. The combination of a high pietyindex and a low correlation suggested that it was necessary to addressadditional concerns. These additional characteristics required specializedinvestigation to be revealed. The establishment of the IKS was essential,particularly if it served as an evaluation system and measuring tool for theaccomplishment of national character building.